The Influence of Buton Tailing and Expanded Polystyrene (EPS) on The Shear Strength of Sandy Soil - Dewi Amalia; Elrich Gratiawan WD Gulo; Hendry Hendry; Putu tantri Kumala sari; Abdallh Lhwaint (Department of Civil Engineering, Politeknik Negeri Bandung, 2025)
Buton tailings, which are a by-product of Buton asphalt, have not been optimally utilized. In fact, research shows that Buton tailings have the potential as an additive to improve soil characteristics, especially sandy soil. This study aims to analyze the effect of the addition of Buton tailings and Expanded Polystyrene (EPS) on the shear strength of sandy soil. The sandy soil used came from Padalarang, Indonesia. Tests were conducted by adding Buton tailings at 0%, 2.5%, 5%, 7.5%, 10%, and 12.5% of the soil weight, and EPS at 0.15%, 0.3%, and 0.45%. The results showed that the addition of Buton tailings increased the cohesion and shear angle of sand soil. The most significant increase occurred with the addition of 5% Buton tailings and 0.15% EPS which increased the inner shear angle by 44% from the initial condition. Based on these results, it can be concluded that the combination of Buton tailings and EPS has the potential to increase the shear strength of sand soil.